Implementation of Independent Attitude for People with Multiple Disabilities - Wardhani, Rr Dina Kusuma (Universitas Syiah Kuala, 2025)
Multiple disability refers to a condition that refers to multiple impairments, such as a combination of blindness, deafness, or speech impairment. Children with multiple disabilities face significant challenges in communication, learning, and social adjustment. Characteristics of children with multiple disabilities include significant visual and hearing impairments. This research was conducted at SKH MADINAH, Serang, Banten, examining the development of intellectual abilities, behavior, values, and social skills. This research was conducted using a qualitative descriptive approach. The results of this study discuss approaches that can be applied to support children with multiple disabilities in achieving independence, not only in daily activities but also in preparing for long-term life. Through this research, it is hoped that a deeper understanding of the needs of children with multiple disabilities will emerge, as well as strategies to help them become independent individuals, able to adapt, and contribute to their social environment, so that the ability to live independently is greater and provides benefits for these children.